Effects of Different Levels of L-carnitine Supplementation on Egg Quality and Blood Parameters of Laying Japanese Quail - Parizadian, B.; Ahangari, Y.J.; Shargh, M. Shams; Sardarzadeh, A. (International Journal of Poultry Science, 2011)
The objective of present study was to investigate the effects of various levels of L-carnitine on performance, egg quality and blood parameters of laying Japanese quail. This experiment was carried out using 128 quail in a completely randomized design with four levels of L-carnitine (0, 125, 250 and 500 mg/kg). Four replicates with 8 quails were allocated to each experimental treatment and birds were reared from 35-70 days. The results showed that there were no significant differences in feed intake and egg production among experimental treatments (p>0.05). The effect of L-carnitine on feed conversion ratio was significant (p<0.05). The quails were fed with rations containing L-carnitine had lower feed conversion ratio (p<0.05). Adding of L-carnitine supplementation (125 and 250 mg/kg) significantly reduced egg yolk cholesterol and triglyceride (p<0.05). Dietary L-carnitine supplementation had no significant effect on other egg quality parameters (p>0.05). The quails were fed with ration containing L-carnitine supplementation (125 mg/kg) had lower blood triglyceride (p<0.05). Furthermore, L-carnitine at levels of 125 and 500 mg/kg significantly reduced blood cholesterol in comparison with control group (p<0.05). Based on current results, it can be concluded that supplementing diet with L-carnitine will reduce blood triglyceride, cholesterol and improve egg quality in laying Japanese quail.